Multiple single cannulation technique of arteriovenous fistula: A randomized controlled trial - Peralta, R.; Fazendeiro, J.; Pinto, B.; Gonçalves, P.; Sousa, R.; Félix, C.; Carvalho, H.; Vinhas, J.; Ponce, P. (Hemodialysis International, 2022)
Introduction: Despite the impact needling has had on vascular access survival and patient outcome, there is no universal or standardized method proposed for proper cannulation. Rigorous studies are needed, examining cannulation practices, and challenges to achieving complication-free cannulation. Methods: This randomized, open-label trial was conducted at 18 dialysis units owned by a large private dialysis provider operating in Portugal. Eligible patients were adults on chronic hemodialysis, with a new arteriovenous fistula (AVF); cannulated for at least 4 weeks complication-free. Patients were randomly assigned in a 1:1 ratio to one of three cannulation techniques (CT): Multiple Single cannulation Technique (MuST), rope-ladder (RLC), and buttonhole (BHC). The primary endpoint was AVF primary patency at 1 year. Findings: One hundred seventy-two patients were enrolled between March 2014 and March 2017. Fifty-nine patients were allocated to MuST, 56 to RLC, and 57 to BHC. MuST and RLC were associated with a better AVF primary patency than BHC. Primary patency at 12 months was 76.3% in MuST, 59.6% in BHC, and 76.8% in RLC group. Mean AVF survival times were 10.5 months (95% CI = 9.6, 11.3) in the MuST group, 10.4 months (95% CI = 9.5, 11.2) in RLC, and 9.5 months (95% CI = 8.6, 10.4) in BHC. BHC was a significant risk predictor for AVF survival with 2.13 times more events than the other two CT (HR 2.13; 95% CI = 1.07, 4.21; p = 0.03). Discussion: MuST was easy to implement without a diagram and there is no need to use blunt needles. This study showed MuST was efficacious and safe in maintaining the longevity of AVF in dialysis patients.